Functional coating containing inorganic additive and preparation method thereof
By adding modified nanosilicon dioxide and flame retardant ultraviolet absorber to the epoxy resin coating, the problems of poor weather resistance and no flame retardancy of the epoxy resin coating film are solved, and the wear resistance, weather resistance and flame retardant performance of the coating are improved.
Patent Information
- Application Number
- CN202510016152.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-06
- Publication Date
- 2025-04-11
AI Technical Summary
Epoxy resin coating film has poor weather resistance, is susceptible to ultraviolet rays to age and change, and does not have flame retardancy and lacks safety performance.
A functional coating containing inorganic additives is prepared by combining modified nano silica with bisphenol A epoxy resin, nano silica, film forming additives, curing agents, defoaming agents, silane coupling agents, propylene glycol methyl ether acetate and flame retardant ultraviolet absorbers by combining modified nano silica with bisphenol A epoxy resin and adding flame retardant ultraviolet absorbers.
It significantly improves the wear resistance and weather resistance of the coating, prevents aging caused by ultraviolet rays, and has good flame retardant properties, and is not easily affected by external factors.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of coatings, and in particular, relates to a functional coating containing inorganic additives and a preparation method thereof. Background Art
[0002] Epoxy resin is a thermosetting resin. Epoxy resin coatings have strong adhesion and can firmly adhere to various substrates. Therefore, epoxy resin can be used as a film-forming substance for coatings. Coatings prepared with epoxy resin as a film-forming substance have excellent anti-corrosion properties, wear resistance, physical and mechanical properties, electrical insulation and chemical stability. They are widely used in the fields of anti-corrosion, electrical insulation, transportation, and civil construction.
[0003] However, the weather resistance of epoxy resin coatings is poor, and the internal structure of epoxy resin molecules is easily affected by external factors such as ultraviolet rays, resulting in aging and yellowing, and performance degradation. Therefore, epoxy resin cannot be used in environments with strong ultraviolet rays. In addition, epoxy resin does not have flame retardancy and lacks sufficient safety performance. Based on this, the present invention provides a functional coating containing inorganic additives and a preparation method thereof. Summary of the invention
[0004] The object of the present invention is to provide a functional coating containing inorganic additives and a preparation method thereof, so as to solve the problems mentioned in the above background technology.
[0005] The purpose of the present invention can be achieved through the following technical solutions: A functional coating containing inorganic additives, comprising the following raw materials: 100 parts of bisphenol A epoxy resin, 6-12 parts of nano silicon dioxide, 1-3 parts of film-forming aid, 30-40 parts of curing agent, 4-6 parts of defoaming agent, 1.2-2.4 parts of silane coupling agent, 60-80 parts of propylene glycol methyl ether acetate, and 6-8 parts of flame retardant ultraviolet absorber; A method for preparing a functional coating containing an inorganic additive comprises the following steps: The first step is to weigh the raw materials according to the mass proportions: 100 parts of bisphenol A epoxy resin, 6-12 parts of nano silicon dioxide, 1-3 parts of film-forming aid, 30-40 parts of curing agent, 4-6 parts of defoaming agent, 1.2-2.4 parts of silane coupling agent, 60-80 parts of propylene glycol methyl ether acetate, and 6-8 parts of flame retardant ultraviolet absorber; Step 2: Mix nano-silica, silane coupling agent and ethanol solution in a container, add glacial acetic acid to the container to adjust the pH to 3-4, and then heat to react. After the reaction is completed, filter, wash and dry to obtain modified nano-silica; Step 3: adding bisphenol A epoxy resin, film-forming aid, flame retardant ultraviolet absorber, defoamer, and propylene glycol methyl ether acetate into a container and stirring to obtain a mixed coating; Step 4: Add modified nano-silicon dioxide and curing agent to the mixed coating, stir and mix to obtain a functional coating containing inorganic additives.
[0006] Furthermore, the film-forming aid is dipropylene glycol butyl ether.
[0007] Furthermore, the curing agent is one of diethylenetriamine, triethylenetetramine and tetraethylenepentamine.
[0008] Furthermore, the defoaming agent is one of ZY-178, BYK-A530, and ACP-1400.
[0009] Furthermore, the silane coupling agent is silane coupling agent KH-550.
[0010] Furthermore, the ethanol solution used in the second step is an ethanol aqueous solution with a volume fraction of 40-60%, and the amount ratio of the nano-silica, silane coupling agent and ethanol solution used is 6-12 parts: 1.2-2.4 parts: 40-60 parts by mass.
[0011] Furthermore, the heating reaction conditions in the second step are to heat the system temperature to 50-60° C. and react for 4 hours.
[0012] Furthermore, the stirring and mixing condition in the third step is stirring at a rotation speed of 400-600 rpm for 120-150 min.
[0013] Furthermore, the stirring and mixing conditions in the fourth step are stirring at a rotation speed of 300-400 rpm for 60-90 min.
[0014] Furthermore, the flame retardant ultraviolet absorber is prepared by the following steps: Step 1, p-cresol, salicyl chloride, triethylamine, and tetrahydrofuran are mixed in a three-necked flask, a condenser and a thermometer are installed, magnetic stirring is turned on, and the reaction is carried out at a temperature of 60-70°C for 2 hours. After the reaction is completed, the solvent is removed by rotary evaporation, and the rotary evaporation product is washed and dried, and then mixed with aluminum chloride and N,N-dimethylacetamide in a three-necked flask, a condenser and a thermometer are installed, magnetic stirring is turned on, and the reaction is carried out at a temperature of 140-160°C for 6 hours. After the reaction is completed, deionized water is added to the three-necked flask to quench the reaction, and then extracted with ethyl acetate, and then the organic layer is separated by a separatory funnel, and the organic layer is rotary evaporated to remove the solvent to obtain intermediate 1; Step 2, the intermediate 1, N-bromosuccinimide and carbon tetrachloride were mixed in a three-necked flask, a condenser and a thermometer were installed, magnetic stirring was turned on, the system temperature was raised to 75°C, benzoyl peroxide was added to the three-necked flask, and then the reaction was carried out at a temperature of 75°C for 8 hours. After the reaction was completed, vacuum filtration was performed, and the obtained filtrate was rotary evaporated to remove the solvent to obtain the intermediate 2; Step 3: Mix the intermediate 2, trimethyl phosphite and zinc iodide in a three-necked flask, install a condenser and a thermometer, start magnetic stirring, and react at a temperature of 130-140° C. for 6 hours. After the reaction is completed, filter and rotary evaporate the filtrate to obtain the flame retardant ultraviolet absorber.
[0015] Furthermore, the amount ratio of p-cresol, salicylic acid chloride, triethylamine, tetrahydrofuran, aluminum chloride and N,N-dimethylacetamide used in step 1 is 0.1 mol: 0.1 mol: 0.1-0.12 mol: 40-50 mL: 6-10 g: 20-25 mL.
[0016] Furthermore, the usage ratio of intermediate 1, N-bromosuccinimide, carbon tetrachloride and benzoyl peroxide used in step 2 is 0.07 mol: 0.05-0.07 mol: 30-40 mL: 2-2.5 g.
[0017] Furthermore, the usage ratio of intermediate 2, trimethyl phosphite and zinc iodide used in step 3 is 0.05 mol: 0.06-0.08 mol: 3.2 g.
[0018] Beneficial effects of the present invention: The invention uses bisphenol A epoxy resin, nano silicon dioxide, film-forming aid, curing agent, defoaming agent, silane coupling agent, propylene glycol methyl ether acetate and flame retardant ultraviolet absorber as raw materials to prepare a functional coating containing inorganic additives. The invention first modifies nano silicon dioxide with silane coupling agent to carry amino groups, then stirs and mixes propylene glycol methyl ether acetate, bisphenol A epoxy resin, film-forming aid, flame retardant ultraviolet absorber and defoaming agent, and finally adds modified nano silicon dioxide and curing agent to the mixed coating to stir and mix to obtain a functional coating containing inorganic additives. The surface of the modified nano silicon dioxide carries amino groups, which can react with the epoxy group of the bisphenol A epoxy resin to undergo a ring-opening reaction and be combined in the functional coating, thereby greatly improving the wear resistance of the coating. The nano silicon dioxide can also scatter part of ultraviolet light, thereby improving the weather resistance of the functional coating.
[0019] The invention uses p-cresol and salicyl chloride as raw materials, utilizes the hydroxyl group of p-cresol and the acyl chloride group of salicyl chloride to carry out esterification reaction under the condition of triethylamine as an acid binding agent, and then carries out Fries rearrangement under the catalysis of aluminum chloride to obtain intermediate 1, then uses intermediate 1 as raw material and N-bromosuccinimide as a bromination reagent, and carries out halogenation reaction at the benzyl position of intermediate 1 under the action of initiator benzoyl peroxide to obtain intermediate 2, and finally uses intermediate 2 and trimethyl phosphite as raw materials, utilizes the bromomethyl group of intermediate 2 and trimethyl phosphite to carry out Arbuzov reaction to obtain a flame retardant ultraviolet The flame retardant ultraviolet absorber of the present invention has two adjacent hydroxyl groups at the carbonyl position, which can form intramolecular hydrogen bonds with the carbonyl group. After absorbing ultraviolet rays, the intramolecular hydrogen bonds are broken to convert light energy into heat energy for release. Compared with conventional ultraviolet absorbers, the ultraviolet absorber of the present invention can form stronger intramolecular hydrogen bonds and thus has a better ultraviolet absorption effect. In addition, the flame retardant ultraviolet absorber of the present invention also has a phosphate structure, which can decompose at high temperature to produce water vapor to dilute the surrounding oxygen and form a protective carbon layer with heat insulation and oxygen isolation effects, and therefore also has a good flame retardant effect.
[0020] The functional coating containing inorganic additives of the present invention has good wear resistance, excellent adhesion, good acid and alkali corrosion resistance, good weather resistance and flame retardant properties, and is not easily affected by ultraviolet rays and caused by aging. DETAILED DESCRIPTION
[0021] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Example 1
[0022] A flame retardant ultraviolet absorber is prepared by the following steps: Step 1, 0.1 mol of p-cresol, 0.1 mol of salicylic acid chloride, 0.1 mol of triethylamine, and 40 mL of tetrahydrofuran were mixed in a three-necked flask, a condenser and a thermometer were installed, magnetic stirring was turned on, and the reaction was carried out at a temperature of 60°C for 2 hours. After the reaction was completed, the solvent was removed by rotary evaporation, and the rotary evaporation product was washed and dried, mixed with 6 g of aluminum chloride and 20 mL of N, N-dimethylacetamide in a three-necked flask, a condenser and a thermometer were installed, magnetic stirring was turned on, and the reaction was carried out at a temperature of 140°C for 6 hours. After the reaction was completed, deionized water was added to the three-necked flask to quench the reaction, and then extracted with ethyl acetate, and then the organic layer was separated with a separatory funnel, and the organic layer was rotary evaporated to remove the solvent to obtain intermediate 1; Step 2, 0.07 mol of intermediate 1, 0.05 mol of N-bromosuccinimide and 30 mL of carbon tetrachloride were mixed in a three-necked flask, a condenser and a thermometer were installed, magnetic stirring was turned on, the system temperature was raised to 75°C, 2 g of benzoyl peroxide was added to the three-necked flask, and then the reaction was carried out at a temperature of 75°C for 8 hours. After the reaction was completed, vacuum filtration was performed, and the obtained filtrate was evaporated to remove the solvent to obtain intermediate 2; Step 3, 0.05 mol of intermediate 2, 0.06 mol of trimethyl phosphite, and 3.2 g of zinc iodide are mixed in a three-necked flask, a condenser and a thermometer are installed, magnetic stirring is turned on, and the reaction is carried out at a temperature of 130° C. for 6 hours. After the reaction is completed, the reaction is filtered, and the filtrate is rotary evaporated to obtain the flame retardant ultraviolet absorber. Example 2
[0023] A flame retardant ultraviolet absorber is prepared by the following steps: Step 1, 0.1 mol of p-cresol, 0.1 mol of salicylic acid chloride, 0.11 mol of triethylamine, and 45 mL of tetrahydrofuran were mixed in a three-necked flask, a condenser and a thermometer were installed, magnetic stirring was turned on, and the reaction was carried out at a temperature of 65° C. for 2 h. After the reaction was completed, the solvent was removed by rotary evaporation, and the rotary evaporation product was washed and dried, mixed with 8 g of aluminum chloride and 22 mL of N, N-dimethylacetamide in a three-necked flask, a condenser and a thermometer were installed, magnetic stirring was turned on, and the reaction was carried out at a temperature of 150° C. for 6 h. After the reaction was completed, deionized water was added to the three-necked flask to quench the reaction, and then extracted with ethyl acetate, and then the organic layer was separated with a separatory funnel, and the organic layer was rotary evaporated to remove the solvent to obtain intermediate 1; Step 2, 0.07 mol of intermediate 1, 0.06 mol of N-bromosuccinimide and 35 mL of carbon tetrachloride were mixed in a three-necked flask, a condenser and a thermometer were installed, magnetic stirring was turned on, the system temperature was raised to 75°C, 2.2 g of benzoyl peroxide was added to the three-necked flask, and then the reaction was carried out at a temperature of 75°C for 8 hours. After the reaction was completed, vacuum filtration was performed, and the obtained filtrate was evaporated to remove the solvent to obtain intermediate 2; Step 3: Mix 0.05 mol of intermediate 2, 0.07 mol of trimethyl phosphite and 3.2 g of zinc iodide in a three-necked flask, install a condenser and a thermometer, turn on magnetic stirring, and react at a temperature of 135° C. for 6 hours. After the reaction is completed, filter and rotary evaporate the filtrate to obtain the flame retardant ultraviolet absorber. Example 3
[0024] A flame retardant ultraviolet absorber is prepared by the following steps: Step 1, 0.1 mol of p-cresol, 0.1 mol of salicylic acid chloride, 0.12 mol of triethylamine, and 50 mL of tetrahydrofuran were mixed in a three-necked flask, a condenser and a thermometer were installed, magnetic stirring was turned on, and the reaction was carried out at a temperature of 70°C for 2 hours. After the reaction was completed, the solvent was removed by rotary evaporation, and the rotary evaporation product was washed and dried, mixed with 10 g of aluminum chloride and 25 mL of N, N-dimethylacetamide in a three-necked flask, a condenser and a thermometer were installed, magnetic stirring was turned on, and the reaction was carried out at a temperature of 160°C for 6 hours. After the reaction was completed, deionized water was added to the three-necked flask to quench the reaction, and then extracted with ethyl acetate, and then the organic layer was separated with a separatory funnel, and the organic layer was rotary evaporated to remove the solvent to obtain intermediate 1; Step 2, 0.07 mol of intermediate 1, 0.07 mol of N-bromosuccinimide and 40 mL of carbon tetrachloride were mixed in a three-necked flask, a condenser and a thermometer were installed, magnetic stirring was turned on, the system temperature was raised to 75°C, 2.5 g of benzoyl peroxide was added to the three-necked flask, and then the reaction was carried out at a temperature of 75°C for 8 hours. After the reaction was completed, vacuum filtration was performed, and the obtained filtrate was evaporated to remove the solvent to obtain intermediate 2; Step 3, 0.05 mol of intermediate 2, 0.08 mol of trimethyl phosphite, and 3.2 g of zinc iodide are mixed in a three-necked flask, a condenser and a thermometer are installed, magnetic stirring is turned on, and the reaction is carried out at a temperature of 140° C. for 6 hours. After the reaction is completed, the reaction is filtered, and the filtrate is rotary evaporated to obtain the flame retardant ultraviolet absorber.
[0025] Comparative Example 1 This comparative example is a commercially available ultraviolet absorber BP-1.
[0026] The flame retardant ultraviolet absorbers in Examples 1-3 and the commercially available ultraviolet absorber BP-1 in Comparative Example 1 were mixed into bisphenol A epoxy resin at a content of 5% respectively. After the resins of each component were cured, the color difference value (Δe) was tested under the condition of ultraviolet light irradiance of 0.89 W / m2 (300-360 nm) for 168 hours according to the national standard GB / T23987-2009 "Artificial weathering aging of paint and varnish coatings exposed to fluorescent ultraviolet light and water". The test results are shown in Table 1: Table 1 ; It can be seen from Table 1 that the color difference values of the resins in Examples 1-3 after curing are much smaller than the color difference values of the resins in Comparative Example 1 after curing, indicating that the flame retardant ultraviolet absorber of the present invention has better ultraviolet absorption performance than commercially available ultraviolet absorbers. Example 4
[0027] A functional coating containing inorganic additives, comprising the following raw materials: 100 parts of bisphenol A epoxy resin, 6 parts of nano-silicon dioxide, 1 part of dipropylene glycol butyl ether, 30 parts of diethylenetriamine, 4 parts of ZY-178, 1.2 parts of silane coupling agent KH-550, 60 parts of propylene glycol methyl ether acetate, and 6 parts of the flame retardant ultraviolet absorber obtained in Example 1; A method for preparing a functional coating containing an inorganic additive comprises the following steps: The first step is to weigh the raw materials by mass: 100 parts of bisphenol A epoxy resin, 6 parts of nano silicon dioxide, 1 part of dipropylene glycol butyl ether, 30 parts of diethylenetriamine, 4 parts of ZY-178, 1.2 parts of silane coupling agent KH-550, 60 parts of propylene glycol methyl ether acetate, and 6 parts of the flame retardant ultraviolet absorber obtained in Example 1; Step 2: Mix nano-silica, silane coupling agent KH-550, and 40% ethanol aqueous solution by volume in a container, add glacial acetic acid to the container to adjust the pH to 3, then heat the system to 50°C and react for 4 hours. After the reaction is completed, filter, wash, and dry to obtain modified nano-silica. In this step, the nano-silica, silane coupling agent KH-550, and 40% ethanol aqueous solution by volume ratio are 6 parts: 1.2 parts: 40 parts. Step 3: Add bisphenol A epoxy resin, dipropylene glycol butyl ether, the flame retardant ultraviolet absorber obtained in Example 1, ZY-178, and propylene glycol methyl ether acetate into a container and stir at a speed of 400 rpm for 120 minutes to obtain a mixed coating; Step 4: Add modified nano-silica and diethylenetriamine to the mixed coating, stir and mix at a speed of 300 rpm for 60 minutes to obtain a functional coating containing inorganic additives. Example 5
[0028] A functional coating containing inorganic additives, comprising the following raw materials: 100 parts of bisphenol A epoxy resin, 9 parts of nano-silicon dioxide, 2 parts of dipropylene glycol butyl ether, 35 parts of triethylenetetramine, 5 parts of BYK-A530, 1.8 parts of silane coupling agent KH-550, 70 parts of propylene glycol methyl ether acetate, and 7 parts of the flame retardant ultraviolet absorber obtained in Example 2; A method for preparing a functional coating containing an inorganic additive comprises the following steps: The first step is to weigh the raw materials by mass: 100 parts of bisphenol A epoxy resin, 9 parts of nano-silicon dioxide, 2 parts of dipropylene glycol butyl ether, 35 parts of triethylenetetramine, 5 parts of BYK-A530, 1.8 parts of silane coupling agent KH-550, 70 parts of propylene glycol methyl ether acetate, and 7 parts of the flame retardant ultraviolet absorber obtained in Example 2; Step 2: Mix nano-silica, silane coupling agent KH-550, and 50% ethanol aqueous solution by volume in a container, add glacial acetic acid to the container to adjust the pH to 3.5, then heat the system to 55°C and react for 4 hours. After the reaction is completed, filter, wash, and dry to obtain modified nano-silica. In this step, the nano-silica, silane coupling agent KH-550, and 50% ethanol aqueous solution by volume ratio are 9 parts: 1.8 parts: 50 parts. Step 3: Add bisphenol A epoxy resin, dipropylene glycol butyl ether, the flame retardant ultraviolet absorber obtained in Example 2, BYK-A530, and propylene glycol methyl ether acetate into a container and stir at a speed of 500 rpm for 135 minutes to obtain a mixed coating; Step 4: Add modified nano-silica and triethylenetetramine to the mixed coating, stir and mix at a speed of 350 rpm for 75 minutes to obtain a functional coating containing inorganic additives. Example 6
[0029] A functional coating containing inorganic additives, comprising the following raw materials: 100 parts of bisphenol A epoxy resin, 12 parts of nano silicon dioxide, 3 parts of dipropylene glycol butyl ether, 40 parts of tetraethylene pentamine, 6 parts of ACP-1400, 2.4 parts of silane coupling agent KH-550, 80 parts of propylene glycol methyl ether acetate, and 8 parts of the flame retardant ultraviolet absorber obtained in Example 3; A method for preparing a functional coating containing an inorganic additive comprises the following steps: The first step is to weigh the raw materials by mass: 100 parts of bisphenol A epoxy resin, 12 parts of nano silicon dioxide, 3 parts of dipropylene glycol butyl ether, 40 parts of tetraethylene pentamine, 6 parts of ACP-1400, 2.4 parts of silane coupling agent KH-550, 80 parts of propylene glycol methyl ether acetate, and 8 parts of the flame retardant ultraviolet absorber obtained in Example 3; Step 2: Mix nano-silica, silane coupling agent KH-550, and 60% ethanol aqueous solution by volume in a container, add glacial acetic acid to the container to adjust the pH to 4, then heat the system to 60°C and react for 4 hours. After the reaction is completed, filter, wash, and dry to obtain modified nano-silica. In this step, the amount ratio of nano-silica, silane coupling agent KH-550, and 60% ethanol aqueous solution by volume is 12 parts: 2.4 parts: 60 parts. Step 3: Add bisphenol A epoxy resin, dipropylene glycol butyl ether, the flame retardant ultraviolet absorber obtained in Example 3, ACP-1200, and propylene glycol methyl ether acetate into a container and stir for 150 minutes at a speed of 600 rpm to obtain a mixed coating; Step 4: Add modified nano-silicon dioxide and tetraethylenepentamine to the mixed coating, stir and mix at a speed of 400 rpm for 90 minutes to obtain a functional coating containing inorganic additives.
[0030] Comparative Example 2 A functional coating containing inorganic additives, comprising the following raw materials: 100 parts of bisphenol A epoxy resin, 12 parts of nano silicon dioxide, 3 parts of dipropylene glycol butyl ether, 40 parts of tetraethylene pentamine, 6 parts of ACP-1400, 2.4 parts of silane coupling agent KH-550, and 80 parts of propylene glycol methyl ether acetate; A method for preparing a functional coating containing an inorganic additive comprises the following steps: The first step is to prepare 100 parts of bisphenol A epoxy resin, 12 parts of nano-silicon dioxide, 3 parts of dipropylene glycol butyl ether, 40 parts of tetraethylene pentamine, 6 parts of ACP-1400, 2.4 parts of silane coupling agent KH-550, and 80 parts of propylene glycol methyl ether acetate by mass; Step 2: Mix nano-silica, silane coupling agent KH-550, and 60% ethanol aqueous solution by volume in a container, add glacial acetic acid to the container to adjust the pH to 4, then heat the system to 60°C and react for 4 hours. After the reaction is completed, filter, wash, and dry to obtain modified nano-silica. In this step, the amount ratio of nano-silica, silane coupling agent KH-550, and 60% ethanol aqueous solution by volume is 12 parts: 2.4 parts: 60 parts. Step 3: Add bisphenol A epoxy resin, dipropylene glycol butyl ether, ACP-1200, and propylene glycol methyl ether acetate into a container and stir at a speed of 600 rpm for 150 minutes to obtain a mixed coating; Step 4: Add modified nano-silicon dioxide and tetraethylenepentamine to the mixed coating, stir and mix at a speed of 400 rpm for 90 minutes to obtain a functional coating containing inorganic additives.
[0031] Comparative Example 3 This comparative example is a commercially available epoxy resin wear-resistant coating.
[0032] The functional coatings containing inorganic additives in Examples 4-6 and Comparative Example 2 and the commercially available epoxy resin wear-resistant coating in Comparative Example 3 were tested for wear resistance according to the national standard GB23988-2009 "Falling Sand Method for Determination of Wear Resistance of Coatings", and the flame retardant properties of the coatings were tested according to UL94. The test results are shown in Table 2: Table 2 ; It can be seen from Table 2 that the functional coating containing inorganic additives of the present invention in Examples 4-6 has a lower wear rate and a higher flame retardant grade than the commercially available epoxy resin wear-resistant coating, indicating that the functional coating containing inorganic additives of the present invention has better wear resistance and flame retardant properties, while the functional coating containing inorganic additives in Comparative Example 2 was not added with the flame retardant UV absorber of the present invention during preparation, and although it still has excellent wear resistance, it does not have flame retardant properties.
[0033] The above is a detailed introduction to a functional coating containing inorganic additives and a preparation method thereof provided by the present invention. Specific examples are used herein to illustrate the principles and implementation methods of the present invention. The description of the above embodiments is only used to help understand the method of the present invention and its core ideas, including the best mode, and also enables any technician in the field to practice the present invention, including the manufacture and use of any device or system, and the implementation of any combination method. It should be pointed out that for ordinary technicians in this technical field, the present invention can also be improved and modified in a number of ways without departing from the principles of the present invention. In particular, as long as there is no structural conflict, the various features in the embodiments disclosed in the present invention can be used in combination with each other in any way. The fact that these combinations are not exhaustively described in this specification is only for the purpose of omitting space and saving resources. Therefore, the present invention is not limited to the specific embodiments disclosed herein, but includes all technical solutions falling within the scope of the claims.
Claims
1. A functional coating containing inorganic additives, characterized in that: The invention comprises the following raw materials in parts by weight: 100 parts of bisphenol A epoxy resin, 6-12 parts of nano silicon dioxide, 1-3 parts of film-forming aid, 30-40 parts of curing agent, 4-6 parts of defoaming agent, 1.2-2.4 parts of silane coupling agent, 60-80 parts of propylene glycol methyl ether acetate, and 6-8 parts of flame retardant ultraviolet absorber; Wherein, the flame retardant ultraviolet absorber is prepared by the following steps: Step 1, p-cresol, salicyl chloride, triethylamine and tetrahydrofuran are mixed in a container, stirred evenly, reacted at a temperature of 60-70°C for 2h, and after the reaction, the solvent is removed by rotary evaporation, and the rotary evaporation product is washed and dried, mixed with aluminum chloride and N,N-dimethylacetamide in a container, stirred evenly, and reacted at a temperature of 140-160°C for 6h to obtain intermediate 1; Step 2, intermediate 1, N-bromosuccinimide and carbon tetrachloride are mixed in a container, stirred evenly, the system temperature is raised to 75° C., benzoyl peroxide is added to the container, and then reacted at 75° C. for 8 h to obtain intermediate 2; Step 3: Mix the intermediate 2, trimethyl phosphite and zinc iodide in a container, stir evenly, and react at a temperature of 130-140° C. for 6 hours to obtain the flame retardant ultraviolet absorber.
2. The functional coating containing inorganic additives according to claim 1, characterized in that: The amount ratio of p-cresol, salicyl chloride, triethylamine, tetrahydrofuran, aluminum chloride and N,N-dimethylacetamide used in step 1 is 0.1 mol: 0.1 mol: 0.1-0.12 mol: 40-50 mL: 6-10 g: 20-25 mL.
3. The functional coating containing inorganic additives according to claim 1, characterized in that: The usage ratio of intermediate 1, N-bromosuccinimide, carbon tetrachloride and benzoyl peroxide used in step 2 is 0.07 mol: 0.05-0.07 mol: 30-40 mL: 2-2.5 g.
4. The functional coating containing inorganic additives according to claim 1, characterized in that: The usage ratio of intermediate 2, trimethyl phosphite and zinc iodide used in step 3 is 0.05 mol: 0.06-0.08 mol: 3.2 g.
5. A method for preparing a functional coating containing inorganic additives as claimed in any one of claims 1 to 4, characterized in that: The following steps are involved: The first step is to weigh the raw materials according to the mass proportions: 100 parts of bisphenol A epoxy resin, 6-12 parts of nano silicon dioxide, 1-3 parts of film-forming aid, 30-40 parts of curing agent, 4-6 parts of defoaming agent, 1.2-2.4 parts of silane coupling agent, 60-80 parts of propylene glycol methyl ether acetate, and 6-8 parts of flame retardant ultraviolet absorber; Step 2: Mix nano-silica, silane coupling agent and ethanol solution in a container, add glacial acetic acid to the container to adjust the pH to 3-4, and then heat to react. After the reaction is completed, filter, wash and dry to obtain modified nano-silica; Step 3: adding bisphenol A epoxy resin, film-forming aid, flame retardant ultraviolet absorber, defoamer, and propylene glycol methyl ether acetate into a container and stirring to obtain a mixed coating; Step 4: Add modified nano-silicon dioxide and curing agent to the mixed coating, stir and mix to obtain a functional coating containing inorganic additives.
6. The method for preparing a functional coating containing inorganic additives according to claim 5, characterized in that: The film-forming aid is dipropylene glycol butyl ether, and the curing agent is one of diethylenetriamine, triethylenetetramine and tetraethylenepentamine.
7. The method for preparing a functional coating containing inorganic additives according to claim 5, characterized in that: The defoaming agent is one of ZY-178, BYK-A530 and ACP-1400, and the silane coupling agent is silane coupling agent KH-550.
8. The method for preparing a functional coating containing inorganic additives according to claim 5, characterized in that: The ethanol solution used in the second step is an ethanol aqueous solution with a volume fraction of 40-60%. The amount ratio of the nano-silicon dioxide, silane coupling agent and ethanol solution used is 6-12 parts by mass: 1.2-2.4 servings: 40-60 servings.
9. The method for preparing a functional coating containing inorganic additives according to claim 5, characterized in that: The heating reaction conditions in the second step are to heat the system temperature to 50-60°C and react for 4 hours.
10. The method for preparing a functional coating containing inorganic additives according to claim 5, characterized in that: The stirring and mixing conditions in the third step are stirring at a rotation speed of 400-600 rpm for 120-150 min, and the stirring and mixing conditions in the fourth step are stirring at a rotation speed of 300-400 rpm for 60-90 min.
Citation Information
Patent Citations
Preparation method of impact-resistant protective water-based paint for helmets
CN116478593A
Ultrathin fireproof water-based paint and preparation method thereof
CN118852917A
Environment-friendly water-based strippable coating and preparation method thereof
CN118995027A
Environment-friendly waterproof coating and preparation method thereof
CN119177080A